IMPLEMENTASI BASIS DATA UNTUK PENGOLAHAN DATA PENJUALAN DI TOKO CINSPEED STORE - Inggried Rillya Sondakh; Rahellea Joiby Onibala; Kristofel Santa (Program Studi Informatika Universitas PGRI Yogyakarta, 2026)
This study analyzes the implementation of a database in processing sales data at Cinspeed Store, a business selling motorcycle parts and equipment. Traditional methods often cause problems such as data loss risk, inconsistency, and data duplication, which impede service speed and financial report accuracy. The database serves as a fundamental solution due to its ability to store data centrally, structured, and organized, allowing for more systematic sales data processing. The methodology used is qualitative, with data collected through observation, interviews, and document analysis. The findings indicate that the database is designed with four main interconnected entities: Goods, Sales, Customer, and Employee, to maintain consistency and prevent information duplication. This implementation successfully overcomes the limitations of manual methods. The computerized system enables the store owner to monitor daily sales trends and track stock availability in real-time. This accurate information becomes the strategic foundation for decision-making, such as inventory control and sales evaluation. In conclusion, the database is an essential component that enhances the accuracy and efficiency of daily sales data management.